Effects of superfine grinding on micromeritic properties of Eucommia ulmoides Oliv. leaves (Bangladesh Journal of Botany, 2020)
Effects of regular grinding and superfine grinding on the micromeritic properties of Eucommia ulmoides leaves were investigated. Coarse powder 1 (5732 nm), 2 (4784.67 nm), 3 (4133.67 nm), 4 (2119 nm) were prepared by regular grinding. Superfine powder 5 (1310.67 nm) was prepared by superfine grinding, all the particle sizes presented normal distribution. Results showed that Eucommia ulmoides leaf powders have smaller size, greater bulk density and smaller angle of repose. The water solubility index values, water holding capacity value and oil binding capacity value were significantly improved as the size decreases. Furthermore, biological microscopy revealed the surface morphology of five powders. FT-IR analysis showed the nature of Eucommia ulmoides leaves unchanged. These results showed that the physicochemical and functional properties of Eucommia ulmoides leaves can be improved by superfine grinding, which would be more suitable for the development of functional compounds than native Eucommia ulmoides leaves.